(untitled) (Research, Society and Development, 2022)
The expression “psychotropic” is of origin, “Psycho” refers to the psychic dimension of the individual and “tropic” comes from tropism, that is, attraction to something. The present study aimed to identify the risk factors for drug overdose of the psychotropics, fluoxetine and amitriptyline. The present study is a descriptive research, literature review of a bibliographic nature, carried out through investigations in articles in electronic journals, VHL, SCIELO, LILACS and ANVISA. Amitriptyline is a tricyclic antidepressant that blocks alpha-adrenergic receptors, anticholinergics lead to cardiotoxicity, resulting in hypotension and arrhythmias that can lead to death of the patient, life threatening is manifested with an overdose of 100 mg. Fluoxetine is a selective serotonin reuptake inhibitor, which increases serotonin at a high rate, providing feelings of pleasure. tachycardia, tremor, drowsiness, nausea, vomiting. Thus, the importance of the pharmacist’s intervention arises, it has a prominent role when it comes to the rational use of medicines.